PELAKSANAAN PTMT MELALUI PENERAPAN GELIGA (GERAKAN LITERASI SMA NEGERI 3 KUALA) UNTUK MENGATASI LEARNING LOSS SEMASA PANDEMI COVID-19 - Cut Sazuana Maqfirah (Jurnal Real Riset, 2022)
The purpose of the article is to fulfiil student learning resources and increase reading interest in SMA Negeri 3 Kuala students while still following health protocols. The program is called “geliga”. The term “geliga” was born from the word Gerakan Literasi at SMA Negeri 3 Kuala. The method used is through procedurs, planning, implementation, and ploblem solving. The results of the Geliga implementation activities to increase the reading interest of students of SMA Negeri 3 Kuala in the form of students becoming more fond of reading and frequent visits to the library. In addition, students are able to practice memory to rewrite books that have been read.Keywords : Literacy Movement, Reading Interest